The Security Impact of Sudanese Refugees in Eastern Chad (Journal of Governance and Development (JGD), 2023)
The current refugee’s crises across Africa, Middle East and Asia havecaptured the world’s attention. Much of the existing discourse has stemmedfrom developed nations and focused on the economic and humanitarianimpacts that these lingering crises had on the developed countries. Thisstudy being a deviation from the previous studies, investigate the securityimpact of Sudanese refugees in the Eastern Chad. This study used literaturesourced materials and internet resources to examine the security challengesof Sudanese refugees in Eastern Chad by exploring the existing academicand popular literature around historical and contemporary case studies.This is undertaken with a view to overcome the negative effect of refugees onsocial and environmental implications, economic implications and violentconflict implications of refugees on the host nation. The study recommendsthat for peace and stability to be ensure efficient and purposive governanceleadership that will protect lives and property should be provided, provisionof sufficient infrastructure to ease the discomfort of the refugees, andprovision of vocations to provide the refugees with gainful employment thatwill guarantees provision of sustainable livelihood for the displaced victims.The recommendations issued in the paper is of immense importance to thepolicy maker and the various stakeholders involved in the management ofrefugee’s crises in Eastern Chad and beyond.